Idiopathic hypoplasia of the masseter muscle: A case report. Issue 3 (4th May 2017) - Cossellu, Gianguido; Farronato, Marco; Biagi, Roberto; Assandri, Fausto; Farronato, Giampietro
Abstract : Objective and importance: Hypoplasia of the masseter muscle is a rare condition, described as partial or total, associated with congenital malformations or pathologies. Rare cases are those with no genetic alterations in their familiar picture. The authors present a case of an idiopathic masseter muscle hypoplasia in the absence of other pathologies. Clinical presentation: The case report involved a patient who presented to the consultant clinic complaining of facial asymmetry. The patient underwent several exams to confirm the diagnosis of masseter muscle hypoplasia, which included an X-ray, magnetic resonance of the temporomandibular articulation, and electromyography. Intervention: The patient was treated with a customized functional appliance and fixed orthodontic treatment with satisfactory functional and esthetic results. Conclusion: The case presented highlights the possibility of finding a hypoplasia of the masseter muscle even in the absence of other pathologies and without specific clinical symptoms, and how to plan an appropriate treatment with functional appliance and fixed orthodontic therapy.